Factors Affecting Academic Achievement of B.Sc. Students of Tribhuvan University Constituent Campuses in Province - 1, Nepal. - Ghimire, Roma (Himalayan Journal of Science and Technology, 2023)
An attempt has been made to assess the factors affecting academic achievements of bachelor’s level students under Institute Science and Technology of Tribhuvan University in Province No. 1, Nepal. The academic achievement has been considered as a dependent variable and the gender, caste/ethnicity, socio-economic status and learning facilities as independent variables. A cross-sectional research design was used. The sample size of this research was 130 and the sample was drawn using simple random sampling technique. A well-designed questionnaire was used to collect the data. The Binary logistic regression model was used to find the association of various factors with the academic achievement of the students and the goodness of fit test of the model was assessed through Hosmer and Lemeshow test. The study concluded that the internet facility at libraries, as a learning facility, contributed significantly to the students’ academic achievement whereas the remaining variables had no significant effect on the academic achievement of students’ Moreover, this research also discusses the implications for improving academic achievement.